Isolation, identification, and production optimization of natural functional pigments produced by Talaromyces atroroseus LWT-1 - Xian Xia; Xian Xia; Li-Yu Liu; Miao Liu; Guo-Jun Hu; Wen-Ting Li; Zi-Yi Wang; Yao Pei; Yan-He Li; Jing-Jing Li; Yan-Xiang Wang; Xiao-Shan Shi; et al. (Frontiers in Microbiology)
Natural microbial pigments are gaining attention for their potential in various applications due to their safety and sustainability. In this study, we isolated a high-yielding pigment-producing fungus identified as Talaromyces atroroseus LWT-1. The predominant pigment compounds were isolated from the culture extract of T. atroroseus LWT-1 through various chromatographic methods and identified as talaroconvolutins A (1) and B (2), and talarofuranone (3). Compounds 1 and 3 exhibited cytotoxic activity against MCF7, Huh-7, and H446 lines with IC50 values ranging from 0.68 ± 0.09 to 4.19 ± 0.71 μM. In contrast, compound 1 was non-toxic to BEAS-2B cells and significantly promoted their proliferation. To optimize pigments yield, we conducted a series of single-factor and orthogonal experiments to determine the optimal fermentation conditions. The optimal conditions were determined to be: SDA culture medium, 32°C incubation temperature, 170 rpm shaking speed, 60 mL working volume in a 250 mL flask, and a culture duration of 120 h.